Comprehensive assessment of a post-coronary bypass graft patient with cardiovascular magnetic resonance imaging and multi-detector computed tomography - Pairoj Rerkpattanapipat (2018)
Coronary bypass graft surgery (CABG) is a revascularization procedure which reduces myocardial ischemia and cardiovascular morbidity and mortality in selected patients; however, up to 40% of saphanous vein grafts may degenerate over 10 years. Although coronary angiography is the gold standard to detect graft patency and native vessel disease, sometimes it is difficult to locate the grafts resulting in increased exposure to radiation and contrast administration. This case highlights the utility of cardiac computerized tomography and magnetic resonance imaging to provide comprehensive noninvasive assessment in a patient post CABG.